Loving or loathing? A power‐dependency explanation for narcissists' social acceptance in the workplace. (2nd February 2022) - Xu, Erica; Huang, Xu; Robinson, Sandra L.; Ouyang, Kan
Summary: Research on the social consequences of narcissism points to an intriguing paradox: narcissists are socially aversive and destructive to healthy interpersonal relationships; yet, narcissists also have an ability to be socially magnetic and attractive. This raises the question we seek to answer in this paper: Are narcissists socially accepted by coworkers in the workplace, and if so, when? Drawing on the social‐constructionist perspective and power‐dependence theory, we propose that others' dependency on narcissists plays a critical role in determining narcissists' social acceptance in the workplace. Results from two time‐lagged independent studies suggest that narcissists with a high level of expertise status experience less ostracism than non‐narcissists, particularly in a group with high group goal interdependence; by contrast, narcissists who are perceived to lack expertise status experience greater ostracism than non‐narcissists, particularly in a group with low group goal interdependence. In Study 2, in addition to ostracism, we also examined social inclusion and popularity of narcissists, and we found that narcissists with high expertise status are more likely to be social included and to become popular, particularly in a group with a high level of group goal interdependence.